Gender, body and sexuality in All about my mother and The skin I have in, of Pedro Almodóvar - Paloma Coelho; Juliana Gonzaga Jayme (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
This article aims to reflect on the construction of gender relations in contemporary cinema from the analysis of movies All about my mother (1999) and The skin I have in (2011), of Pedro Almodóvar. Has already been discussed in other academic works, All about my mother is a film of great repercussion in cinematographic circuit, and at the same time, it is a fertile field for the analysis of gender relations in the cinema by presenting an innovative approach on the subject, subverting cinematic conventions and standards socially imposed in relation to gender and family. More than a decade later, in The skin I have in, the director proposes a discussion even more sophisticated, addressing not only the process of change of sex, as also the complexity and the transitoriness of gender categories and body, demonstrating its constructive character and unfinished and, therefore, detached from fixed categorizations and essentialist. Hence, it is intended to discuss how these movies are questioning the notions of male and female by approaching them as cultural constructions and disrupting some social standards of “normality” and “abnormality” to deconstruct aspects often understood as natural and universal on the performance of gender.